INTERSYSTEM APPROACH TO THE ASSESSMENT OF ADAPTIVE MECHANISMS OF THE ADOLESCENT'S ORGANISM - Ludmila Dmitrievna Tsaturyan; Radmila Hamitovna Kuvandykova (Наука. Инновации. Технологии)
The article discusses the state of adaptation mechanisms in adolescent boys, taking into account intersystem approach. Studied the correlation of the vegetative regulation of heart rate and levels of cortisol, testosterone, estradiol in blood serum of adolescents Russian and Turkmen nationality. The Russians have installed more adolescents expressed positive inter-correlation of cortisol with indices of LF, VLF, AMo, SI and negative - with SDNN, RMSSD, pNN50, HF, while the Turkmen boys similar relation was less pronounced. Relationship testosterone levels in both population groups were positive with heart rate, AMo, SI, VLF and negative - with SDNN, RMSSD, pNN50, HF. The established relationship of estrogen with HRV reflects the peculiarities of the heart rhythm regulation among Turkmen boys, probably due to the relatively low estradiol level mediated the influence of estrogen on the cardiovascular system (positive relationship with HR, SI, VLF, and negative - with SDNN, RMSSD, pNN50, HF).